“Producción de tres variedades de fréjol Phaseolus vulgaris L. en asociación con el cultivo de Café.”. - Bone Cabrera, Jonathan Wladimir (2020)
Coffee production in Ecuador is being reactivated due to the demand of international markets and it is by fact that it is about encouraging the farmer to plant new varieties of coffee but with polyculture practices that is, in association with corn, beans or vegetables developing Thus, an agroecological system favorable to the soil-plant-man-environment interaction, for this reason the production of three varieties of beans Phaseolus vulgaris L. was established in association with the cultivation of coffee in the Sacha Wiwa experimental center of the Guasaganda parish of the canton The Mana. Two varieties of 40-year-old beans and pigeon leg were established associated with six coffee varieties from the Cofenac group, Napo Payamino and Estación Tropical, a random complete block design was used, the variables to be evaluated were: germination percentage, plant height (cm) of beans and coffee; weight of 100 seeds, weight of grains (g) and benefit-cost ratio. In the germination percentage both beans obtained 95%, highlighting in the variables plant height, weight of 100 seeds and weight of grains the 40-year-old bean. The best benefit-cost ratio was obtained by beans in their forties with 0.37. In the height of coffee plants, the variety that stood out was COF06 with 95.22 cm and a relative growth rate of 0.18 cm day-1.